Implementing regional blue economy research and innovation strategies: a case study for the Black Sea - Salihoglu, Baris; Yücel, Mustafa; Uygurer, Pinar; Yücel, Ezgi Şahin; Papathanassiou, Evangelos; Tezcan, Devrim; Stanica, Adrian; Stanciu, Irina; Moncheva, Snejana Petrova; Dzhembekova, Nina; Blagovestova Stefanova, Kremena; Komorin, Viktor; et al. (Frontiers in Marine Science, 2024)
The Black Sea is a vital resource with vast potential to boost the societal value of the Blue Economy for its surrounding countries. Improved knowledge and enhanced infrastructure together with better coordination and alignment of research and innovation efforts are critical for the better management of the deteriorated Black Sea ecosystem to help restore and maintain its resilience and enable sustainable use of natural resources. In 2019, the Black Sea Strategic Research and Innovation Agenda (Black Sea SRIA), was developed by the Black Sea experts, in cooperation with European marine institutes and organizations, with the support of the European Commission. Black Sea SRIA presents the priorities and ecosystem-based management options needed for a healthy, sustainable, and resilient Black Sea. Since 2019, efforts focused on developing concrete actions under the Black Sea SRIA Implementation Plan (IP) to contribute to the national blue economy strategies, better structuring of the relevant funding mechanisms for solution-oriented implementation and the international and regional strategies, supporting the co-funding mechanisms. In this study, we present a transnational process that has led to the development of the IP which utilized a bottom-up, co-design and co-creation-based approach. The SRIA and its IP support better governance of the blue economy principles towards sustainable development and conservation of unique Black Sea ecosystems. The Black Sea SRIA and IP address the fundamental research challenges of the region, promote the blue economy, and also build vital support systems and innovative research infrastructure and capacity together with academia, funding organizations, industry, policy, civil society and local communities. The IP is a long-lasting guide to catalyze new ideas and innovations towards and with the Black Sea community with strong implications for other sea basins.